Hollow mesoporous polymer capsules with Dihydroartemisinin and Chloroquine diphosphate for knocking down Plasmodium falciparum infection - Medhi H.; Maity S.; Suthram N.; Chalapareddy S.K.; Bhattacharyya M.K.; Paik P. (My University, 2025)
Plasmodium falciparum is resistant to all antimalarial drugs and a challenge for treatment. With this respect, formulations of antimalarial drugs with polymeric capsules with nanostructure carry a significant signature to suppress the resistance and to kill the Plasmodium falciparum. In this work, idiosyncratic hollow mesoporous polycaprolactone (ihmPCL) capsules were designed through ultrasonic-template synthesis approach with hollow core of dia. ca. ∼ 450 nm and shell thickness of ca. ∼ 30 nm and pore size of ca. ∼ 8-9 nm. Then two formulations of ihmPCL capsules with Dihydroartemisinin (DHA) and Chloroquine diphosphate (CQDP) have been developed. ihmPCL capsules are capable to load 200.0 μg of DHA and 18.6 μg of CQDP per mg of capsules. With this formulation we can empowered to tune the doses of DHA and CQDP with time and temperature (30 °C-43 °C). It is observed that up to 143.20 μg (∼71.6%) of DHA and 17.71 μg (∼95.2%) of CQDP release can be controlled at different essential conditions which further can be sustained for longer period of time. Further, the half-maximum inhibitory concentration (IC50) have been investigated with these formulations and calculated to be 66.60 nM and 25.14 nM for DHA and CQDP, respectively in P. falciparum inhibition in vitro. Based on the unique release behaviour of these antimalarial drugs a 'temperature clock' module have been proposed for further accelerate the inhibition rate of P. falciparum infection. In conclusion, the PCL-DHA and PCL-CQDP formulations developed in this work could be effective in knocking down the P. falciparum infection and is paramount for treatment of malaria. © 2018 IOP Publishing Ltd.